The protection of weak part of contract against cheating - Krawczyk, Michał (Management and Administration Journal, 2023)
This article concerns the civil code regulations used in appeals in courts and the jurisdiction of the Highest Court. It discusses the institution of civil law, especially article 388 of the civil code, which protects the weak part of a contract against cheating.